The effectiveness of adjusting resistance training loads through velocity-based techniques in experienced sprinters: a case series study - Muñoz de la Cruz, Violeta; Agudo-Ortega, Aarón; Sorgente, Vincenzo; Turner, Anthony P.; González-Ravé, José María (Frontiers in Physiology, 2023)
This study aimed to determine if adjusting the loads via velocity-based training (VBT) in each session is more efficient in monitoring the relative intensity than programming loads assessing 1RM pretraining. To achieve this, six national level sprinters were randomly divided into two groups, i.e., adjusting loads (AL, n=3) and not adjusting loads (NAL, n=3), during twelve sessions of a squat training (ST) program. During this training intervention, the AL group adjusted the intensity for each session in the squat exercise depending on the speed the load was lifted after warmup. The NAL group, instead, progressed in the squat exercise referring to the 1RM estimated at pre-test. In addition, Parallel Squat (PSQ), Countermovement Jump (CMJ), Squat Jump (SJ), 30m sprint standing start (30S) and 30m sprint flying start (30F) tests were carried out before and after conducting the ST program.Interestingly, AL performed the ST near their estimated velocities at 70 -75 %1RM, however with a wider gap at 80 -85 %1RM. The NAL group, instead, did not presented such a detectable behaviour across the whole ST. Moreover, both groups demonstrated improved performances in PSQ, CMJ and SJ, whereas there were little changes in 30S and 30F after ST. Additionally, AL obtained a greater effect size than NAL in PSQ (0.60 vs 0.35) but lower effect size in CMJ, SJ, 30S and 30F (0.41 vs 0.63, 0.30 vs 0.40, 0.04 vs 0.28 and 0.22 vs 0.24). However, percentage change was greater in AL in all tests. Based on these findings, we can conclude that further investigation into the AL strategy in VBT is warranted for sprinter athletes' daily strength practices. The AL technique shows promise as a valuable tool for accurately adjusting and monitoring medium-high training loads to ensure they align with the intended intensity.